Molecular screening of hybrid rice parental lines for bacterial blight resistance genes - RANVIR SINGH GILL, JAGJEET SINGH LORE and RENU KHANNA, RAMANJEET SINGH BRAR* (Indian Phytopathology, 2017)
A set of twenty-nine parental lines of hybrid rice of five CMS lines and twenty-four newly identified elite restorers showing field resistance towards bacterial blight (BB) under artificial inoculation conditions were selected for molecular characterization to detect the presence of anticipated known BB resistance genes. Gene specific primers were used to detect the presence of Xa4, xa13 and Xa21 genes. Nineteen restorer and four CMS lines confirmed the presence of Xa4 gene in homozygous condition exhibiting a resistant band of 150bp. For xa13 gene only twelve restorer lines could show the presence of the gene in homozygous condition exhibiting a resistant band size of 500bp while none of the CMS lines showed the presence of this gene. Thirteen restorer lines and two CMS lines showed the presence of Xa21 gene in homozygous condition with the presence of single band of 1000bp. A total of five restorer lines were identified which had all the BB resistance genes and only two CMS lines showed the presence of two BB resistance genes (Xa4 + Xa21). The comparison of disease reaction of different restorer and CMS lines against all the ten pathotypes of bacterial blight pathogen prevalent in Punjab state indicated that gene combinations Xa4 + xa13 + Xa21, Xa4 + xa13 or xa13 + Xa21 were effective in providing resistance against all Xoo pathotypes. The lines which carried these genes individually had variable reaction against different pathotypes. The information generated in this study will be helpful in the stacking of multiple BB resistance genes especially into CMS lines in order to provide durable resistance against the disease and for the long term sustainability of hybrids.